2013
DOI: 10.1002/ejic.201300504
|View full text |Cite
|
Sign up to set email alerts
|

Rare‐Earth‐Metal‐Promoted Hydroalumination

Abstract: The capability of bis(trimethylsilyl)amidoalane to act as a hydride transfer reagent in organolanthanide chemistry was investigated by probing its reactivity toward alkylyttrium complexes. Reaction with Cp*2YMe(thf) led to the isolation of the bimetallic complex Cp*2Y(μ‐H)2Al(Me)[N(SiMe3)2] (Cp* = 1,2,3,4,5‐pentamethylcyclopentadiene), whereas reaction with [Cp*YMe2]3 gave MeAl[N(SiMe3)2]2 as the only isolable hydride transfer product. The dimeric complex [Cp*Y{N(SiMe3)2}(μ‐H)]2 represents one possible product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…Bridging hydrides were observed in the bimetallic compound [Al( -H)(N{SiMe 3 } 2 ) 2 ] 2 ([12] 2 ) whereas the non-symmetric dimer, Al(N{SiMe 3 } 2 )(NMe 2 )( -NMe 2 ) 2 AlH(N{SiMe 3 } 2 ) (13) contained bridging NMe 2 groups [20]. Recently it was shown that the reaction of 7 with SiMe 3 Cl afforded [12] 2 in 98% isolated yield [21]. The reaction of 12 with YCp* 2 Me(THF) afforded the bimetallic compound YCp* 2 ( -H) 2 AlMe(N{SiMe 3 } 2 ) (14) and Al(N{SiMe 3 } 2 ) 3 (1) [21].…”
Section: Aluminiummentioning
confidence: 97%
See 2 more Smart Citations
“…Bridging hydrides were observed in the bimetallic compound [Al( -H)(N{SiMe 3 } 2 ) 2 ] 2 ([12] 2 ) whereas the non-symmetric dimer, Al(N{SiMe 3 } 2 )(NMe 2 )( -NMe 2 ) 2 AlH(N{SiMe 3 } 2 ) (13) contained bridging NMe 2 groups [20]. Recently it was shown that the reaction of 7 with SiMe 3 Cl afforded [12] 2 in 98% isolated yield [21]. The reaction of 12 with YCp* 2 Me(THF) afforded the bimetallic compound YCp* 2 ( -H) 2 AlMe(N{SiMe 3 } 2 ) (14) and Al(N{SiMe 3 } 2 ) 3 (1) [21].…”
Section: Aluminiummentioning
confidence: 97%
“…Recently it was shown that the reaction of 7 with SiMe 3 Cl afforded [12] 2 in 98% isolated yield [21]. The reaction of 12 with YCp* 2 Me(THF) afforded the bimetallic compound YCp* 2 ( -H) 2 AlMe(N{SiMe 3 } 2 ) (14) and Al(N{SiMe 3 } 2 ) 3 (1) [21].…”
Section: Aluminiummentioning
confidence: 98%
See 1 more Smart Citation
“…Therein, the olefin reacts in a first step with bimetallic complex A to form the mixed alkyl complex C possibly via a four-membered metallacycle intermediate B. Next, alkyl hydride exchange occurs with E to regenerate starting material A and amidoaluminum alkyl F via four-membered metallacycle D [111]. The efficiency of several chiral alkyl or amido yttrium complexes prepared from N-silyl-or N-cyclopentyl-substituted binaphthylamido ligands (cf.…”
Section: Organolanthanide-catalyzed Hydroalumination Hydroamination mentioning
confidence: 99%
“…Lanthanide aluminates, upon activation,a re typicallyc atalyst precursors for alkene and diene polymerization and are also used to generate highly reactive species such as masked alkylidenes and cationic alkyls. [29][30][31][32][33][34][35][36][37][38][39][40] In the few reports of aluminum addition chemistry,p iano-stool scandium compounds catalyze the carboalumination of ether-containing alkynes, [41] and bentsandwich yttrium compounds catalyze hydroalumination, [42] together suggesting that the appropriate ancillary ligands also are required to promote alumination pathways. In the initial phase of this work, we communicatedt hat an eodymium aluminate supported by ac yclopentadienylborate ligand, {Me 2 Al(Ox Me2 ) 2 BPh(C 5 H 4 )}Nd(AlMe 4 ) 2 (1 Nd ;O x Me2 = 4,4-dimethyl-2-oxazoline), is ac atalyst for aluminationo ft erminal alkynes.…”
Section: Introductionmentioning
confidence: 99%